Overview of Ecological Dynamics in Morocco – Biodiversity, Water Scarcity, Climate Change, Anthropogenic Pressures, and Energy Resources – Navigating Towards Ecosolutions and Sustainable Development - Arabi, Mourad; Mechkirrou, Latifa; El Malki, Mohamed; Alaoui, Karima; Chaieb, Amine; Maaroufi, Fatiha; Karmich, Saida (E3S web of conferences, 2024)
In the context of Morocco’s rich biodiversity and pressing environmental challenges, this paper delves into the intricate dynamics of sustainable development in the country. With a focus on biodiversity conservation, water scarcity, climate change impacts, anthropogenic pressures, and energy resource management, Morocco is navigating ecosolutions and sustainable development. This research highlights the critical importance of biodiversity conservation efforts in preserving the nation’s diverse ecosystems while contributing to national development. Challenges such as forest reduction, agricultural water stress, and declining mammal diversity underscore the urgency of conservation actions. Climate change exacerbates issues in oases, impacting agricultural yields and ecosystem health. This paper also addresses the management of mineral resources and waste production, which pose significant challenges to environmental sustainability. Through strategic policies, international engagements, and capacity-building initiatives, Morocco is striving to achieve resilience and sustainability in the face of evolving global dynamics. By integrating governance, environmental diplomacy, and multilateral cooperation, Morocco is laying a robust foundation for economic growth, social progress, and environmental protection. This manuscript provides a comprehensive overview of Morocco’s environmental challenges, innovative solutions, and commitment to sustainable development in a rapidly changing world.